POLICY AND OPERATIONAL GUIDELINE IN HEALTH COMMUNICATION VIA SOCIAL MEDIA BY NATIONAL CANCER INSTITUTE IN NUTRITION FOR CANCER PREVENTION AMONG OFFICE WORKERS - Chaiyasit, Kamon; Tokaew, Wittayatorn; Sridee, Supaporn; Jitthiang, Piyanoot (Journal of Buddhist Anthropology, 2022)
The aim of this research is to study policy and operational guideline in health communication via social media by national cancer institute in nutrition for cancer prevention among office workers in 4 topics, 1) problems and needs for policy and guidance manual of communication, 2) communication management, 3) communication strategy, 4) communication policy and the development of communication on nutrition for cancer prevention in social media platforms by National cancer institute among office workers. This qualitative research used in-depth interviews involving several participants. The study found that the organization must create policy and identify problems and need from the target group. The identification of target group is the important process of policy creation. The organization should set up mission and organizational structure which includes operational protocol for all operation unit in organization. The communication committees should be set up which include nutritionist and communication specialist in the team and communication planning in all platforms of online social media, providing budget and human resource for operation of this communication project. The strategic formulation in social media results in the creation of image and credibility of organization, good strategy is needed to keep up with trends, design content, resulting in credibility and work together with other network partners. National cancer Institute do the online social media communication in nutrition for cancer prevention as a guideline for other health promotion organizations will adapt this communication for promote nutrition for cancer prevention on social media.